Effect of filling materials on microstructure and properties of CMT-laser beam oscillation hybrid welding behavior of dissimilar Al–Mg–Si alloys - J.R. Li; J.M. Yu; L. Wang; F. Vogel; X.N. Wang; X.J. Shen; B.N. Song; H. Nagaumi (Journal of Materials Research and Technology, 2023)
Laser oscillation-assisted cold metal transfer hybrid welding was conducted on 2.0 mm-thick 6082 and a new 6xxx aluminum alloys. The influence of wire composition on microstructure and mechanical properties of the 6082 and new 6xxx alloy joints is studied. Our results show that, due to the difference in surface tension, the cross section of a joint filled with ER4047 wire typically presents a wider U-shape profile, while the ER5183 filled joint shows a relatively narrower V-shape profile. The average grain size of the ER5183 joint is smaller than that of the ER4047 joint. The ER4047 joint exhibits better fluidity, resulting in a higher proportion of high-angle boundaries compared to the ER5183 joint, which we attribute to the higher Si content. Equiaxed grains are also observed near the fusion boundary on the new 6xxx side, while no equiaxed grain formation is observed on the 6082 side. EDS data demonstrates severe elemental segregation in the center of weld and the partially melted zone, suggesting that multiple secondary phases form unevenly within inter-dendritic regions and grain boundaries of α-Al during the welding process. The microhardness of the weld zone and the heat-affected zone on both sides in the ER5183 joint is higher than that of the ER4047 joint. The corrosion test evidences that the ER5183 joint has a slightly better corrosion resistance than the ER4047 joint. Our findings provide a new understanding on joining of dissimilar Al–Mg–Si alloys and guide the selection of appropriate filling materials and welding processes.